Latin America and Africa. Between South-South solidarity and self-interests - Lechini, Gladys (Estudios Internacionales, 2014)
This paper analyzes relations between Latin America and Africa within the context of South -South cooperation through three cases which show different strategies of an impulse-driven policy. Brazil has resorted to a cultural diplomacy, developing a cumulative policy that blossomed during Lula’s Presidency. Argentina started the rapprochement earlier, but without continuity and Venezuela, a late newcomer, has developed its petro-diplomacy with an ideological rhetoric.